10 years of surgery biliary in Montevideo: results - Piacenza, Guillermo; Czarnevicz, Daniel; Ferreira, C. (Cirugía del Uruguay, 1991)
The authors make a statistical revision of 7000 cases of biliar surgery carried on in Montevideo between 1980 and 1989. In order to study them, two groups are taken into account: 1) simple surgery 2) complex surgery, whick includes urgent operations, patients older than 60, and those with main biliar viae involvement